Risk Mitigation in Employment Sector Investment: TAPERA Fund Fertilization KIK Study - Putri, Tania Octavia (UNIVERSITAS PAKUAN, 2025)
AbstractGlobal economic developments have a significant impact on domestic economic activity, increasing the mobility of countries and businesses. In this context, investment-both in the capital market and in the labor sector-is very important. Law No. 4/2016 concerning Public Housing Savings (TAPERA Law) is designed to fulfill the need for decent housing for workers through a housing savings mechanism. This study evaluates the mechanisms for collecting and managing TAPERA funds, as well as the government's role in mitigating investment risks. The main focus is on the management of funds through Collective Investment Contracts (KIK) and the associated risks. This research also discusses the case of unrealized loss experienced by BPJS Ketenagakerjaan due to the impact of the Covid-19 pandemic and the risk mitigation measures applied in the management of TAPERA. Hopefully, this analysis can provide solutions to improve transparency, accountability, and effectiveness of housing fund management, as well as ensure the welfare of workers in Indonesia. This research adopts a normative legal research method that focuses on analyzing laws and regulations as the main approach. Keywords: TAPERA, Collective Investment Contract (KIK), Mitigating Investment Risk